Elementy tradycji literackiej w wierszu dziecięcym - Ostasz, Maria (ANNALES UNIVERSITATIS PAEDAGOGICAE CRACOVIENSIS. STUDIA LINGUISTICA, 2012)
The paper presents the dialogue with tradition in selected poems for children. Children’s poetry most frequently resorts to intertextuality in the form of affective continuation, thematic restitution and stylistic reminiscence. First, remarks on folk tales as traditional literary texts are offered. The analysis of works which enter into the dialogue with oral texts: Warzyła sroczka... (Once a Magpie Was Making Porridge...) by Czesław Janczarski and Dwa Michały (Two Michaels) by Julian Tuwim, is preceded by a review of charactersitic features of folk texts for children on the examples of Kulig w lesie (Sleigh Ride in the Woods) and Panie Boże Wszechmogący (Almighty God). Then, an intertextual analysis of “ptasie wesele” (bird wedding) and two literary texts in which birds feature as humans: Ptasie radio (Bird Radio) by Tuwim and Poczta w lesie (Post Office in the Woods) by Janczarski is conducted. The literary tradition of children’s poetry is presented in terms of topic restitution and stylistic reminiscence. The research conducted shows an unusually vivid dialogue with tradition present in the literature for children.